1996
DOI: 10.1200/jco.1996.14.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment serum squamous cell carcinoma antigen: a newly identified prognostic factor in early-stage cervical carcinoma.

Abstract: The determination of pretreatment serum SCC-ag level provides a new prognostic factor in early-stage disease, particularly in patients with small tumor size. In future trials to assess the value of new treatment strategies, pretreatment serum SCC-ag levels can be used to help identify patients with a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
115
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 27 publications
5
115
1
Order By: Relevance
“…An elevated pretreatment SCC concentration has been found to be an independent risk factor of poor survival in several studies (385, 393, 399, 408, 436 -438 ). The pretreatment SCC concentration was the only independent risk factor of poor survival in an analysis of results for 260 patients with stage IB or IIA disease (393 ). However, in contrast to other reported investigations, lymph node status showed no independent prognostic value in this study (393 ).…”
Section: Nacb Cervical Cancer Panel Recommendation 2: Serum Scc Concecontrasting
confidence: 51%
See 2 more Smart Citations
“…An elevated pretreatment SCC concentration has been found to be an independent risk factor of poor survival in several studies (385, 393, 399, 408, 436 -438 ). The pretreatment SCC concentration was the only independent risk factor of poor survival in an analysis of results for 260 patients with stage IB or IIA disease (393 ). However, in contrast to other reported investigations, lymph node status showed no independent prognostic value in this study (393 ).…”
Section: Nacb Cervical Cancer Panel Recommendation 2: Serum Scc Concecontrasting
confidence: 51%
“…In patients with stage IB or IIA squamous cell cervical cancer, sensitivity of an elevated pretreatment concentration of SCC to detect lymph node metastases ranged from 60% to 87%, with specificity ranging from 41% to 91% (385,391,393,395,408,434 ). In a large series of 414 patients with early stage cervical cancer, elevated pretreatment SCC, large tumor size, and lymphovascular space involvement were independent risk factors for the presence of lymph node metastases (393 ). In another study (n ϭ 401), after controlling for stage, only high concentrations of SCC (i.e., Ͼ10 g/L) were associated with enlarged lymph nodes shown on CT scan (399 ).…”
Section: Prediction Of Lymph Node Metastases and Treatment Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…Pretreatment SCC levels correlate with cellular differentiation, tumour stage and volume, lymph node status and blood vessel invasion (Reynolds et al, 2005). However, there are conflicting reports on the prognostic significance of pretreatment SCC measurements (Scambia et al, 1994;Gaarenstroom et al, 1995;Duk et al, 1996;Ngan et al, 1996;Bolger et al, 1997;Hong et al 1998). In addition, there are no useful markers in cervical adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of this marker correlate well with clinical stages of the disease, the presence or absence of risk factors, the effect of treatment and the course of the disease. [4][5][6] Furthermore, in SCC of the lung, cervix, head and neck or esophagus, the SCCA values were related to tumor stage [7][8][9][10] and were highest in patients with metastases. 11 Cloning of the SCCA cDNA demonstrated that it belongs to the family of serine protease inhibitors (serpins).…”
Section: Introductionmentioning
confidence: 95%